O uso do tempo nas atividades cotidianas e a qualidade de vida de crianças de classe popular - Nunes, Ana Célia (2015)
Children, as well as adults, organize their daily routines based on their role in day-today activities. Studies on use of time are an important tool for the acknowledgment of daily routine of children, hence allowing us to understand habits and behaviours from various social groups. The goal of this study was to describe the use to time of children ages 9 to 12 years of age in their daily routines and quality of life. These children are from four different public schools in the city of Sao Carlos, a municipality located in the central region of the state of Sao Paulo. The study was composed of 108 children, of both genders; 60 were girls, where as 48 were boys. For data collection, we utilized Diary of Activities children s version and the Autoquestionnaire Qualité de Vie enfant Imagé AUQEI, aside from an identification form for each participant. The results from utilizing Diary of Activities children s version show that the majority of their time during weekdays and weekends was dedicated to basic daily activities related to their well being, their homes, and other children. Also noted was the time balance among school, their home chores and other children, leisure, sports, relaxation, and time for their own. These children consider their daily activities important and satisfactory. We observed a positive life quality for 77.8% of participants, being that leisure time was the best rated (98.1% of the participants considered their life quality satisfactory) and autonomy being the greatest category with the highest number of participants with an impaired life-style (72.2%). There had been correlation, regardless of modest magnitude, between the presence of satisfaction and meaning in the daily occupations and good quality of life. Despite the results pointing to a occupational balance, there was less participation in activities that required larger financial expenditure especially in the areas such as extracurricular education, sports, and leisure. The matter of having little divesity in cultural activities, sports, extracurricular activities and leisure, and the expressive amount of time spent on house chores and care of others, do not translate in a negative experience for the youngsters partaken in this study, in all, the deficits in certain areas of occupational performance serve to reassure the need for further investment and greater attention of governmental instances, of private capital and civil society for this population. This research showed the importance of the study of use of time during early childhood, being this a subject linked directly to human engagement. There is a need for further studies that deepen theoric and emperically in the transformations and tendencies of human engagement during childhood and the way how these engagements interact with the quality of life during this period in life.